Cauca leads climate smartness for agriculture in Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Municipal and State authorities in Cauca are promoting and investing in CSA practices aiming to reach approximately 150.000 farmers, as a result of the implementation of the CSV approach, using evidence generation and local empowerment. In addition, the State Government of Cauca approved USD$66 million from the Royalties National Fund to give to CRC (Cauca Environmental Authority) to scale CSA in at least 8 municipalities of the State.